Strengthening of RC beams by ferrocement made with unconventional concrete - Md Jihad Miah (2020)
Some countries in South Asia has very limited availability of natural stones due to geological features, therefore, most of the concrete buildings of the past are made with burnt clay brick aggregates whose strength is rather low those are more vulnerable to collapse due to any extreme loads. However, ferrocement strengthening has several advantages such as good mechanical performance, cost-effectiveness, locally availability of the materials, and simplicity, this latter making available workmanship able to implement such technique (aspect which is very important in developing countries such as Bangladesh). Hence, the paper deals with the efficacy of ferrocement technique in improving the performance of reinforced concrete beams made in low-strength concrete (beam width 230 mm, height 230 mm, and length 2135 mm). The beams are made with unconventional concrete whose strength is about 12.5–13.0 MPa. The flexural tests are performed experimentally and numerically via the finite element software ABAQUS by considering the following loading configurations: (i) 2 point loads placed at L/3, (ii) 2 point loads are to the support, (iii) 2 point loads close to the mid-span, and (iv) 1 load next to the support and 1 load on the mid-span. The experimental results have shown that unsymmetrical loading decreases the overall load carrying capacity and increases the deformability due to the localization of the damage. The ferrocement beams reinforced by steel wire mesh exhibits high ultimate load carrying capacity and more ductile behavior. The outcome of this research can be used for future modeling and for the development of appropriate design guidelines on the strengthening of concrete structures dealing with different loading conditions.